Social Objectives of Microfinance Institutions and Evaluating its Implementation: A Systematic Review - Ghising, Tilak; Modi, Devendra Kumar (International Research Journal of MMC, 2024)
This research explores the social goals of Microfinance Institutions (MFIs), emphasizing their role in empowering underserved groups, including women, rural populations, and micro-entrepreneurs through financial services. Despite their noble intentions, the commercialization of MFIs, influenced by large banking entities, has shifted the focus towards profitability, potentially undermining their mission to alleviate poverty. A systematic literature review conducted from 2010 to 2020 discloses mixed results regarding the relationship between financial sustainability and outreach depth for microfinance institutions (MFIs). The study explores such as balancing financial sustainability and social outreach, mission drift, regulatory hurdles, and governance shortcomings. It underscores the necessity for collaborative regulation, financial literacy, and enhanced governance to maintain the sustainability and efficacy of microfinance efforts. The study highlights the need for MFIs to balance financial sustainability with their social missions, advocating for enhanced governance, regulatory cooperation, and financial literacy to optimize their impact on poverty alleviation and economic inclusion. Academically, it calls for continued research into the trade-offs between profitability and social outreach, and the effectiveness of innovative microfinance interventions.